Supply-Side Readiness of Primary Health Care in the Philippines - World Bank Group (World Bank, Washington, DC, 2019)
Health indicators in the Philippines currently lag well behind what will be expected given the country’s level of economic development. Immunization rates are at their lowest point in 10 years, maternal mortality remains very high, one in three Filipino children suffer from malnutrition, and the noncommunicable disease (NCD) burden is growing. The resulting epidemiologic profile is complex, and an adequate response requires a robust primary health care system. With the introduction and subsequent expansion of the social health insurer, administered by the Philippine health insurance corporation (PhilHealth), the central government has sought to ensure access to a number of high-priority health services, including at the primary level. However, much of the responsibility for implementing the publicly funded health system is at the local level, where capacity and resources differ. This paper seeks to understand the extent to which basic service delivery units (specifically rural health units (RHUs)) have the capacity to deliver the primary health care services mandated by the government.